Two γ-zeins induce the unfolded protein response. Issue 3 (4th August 2021) - Brocca, Lorenzo; Zuccaro, Melania; Frugis, Giovanna; Mainieri, Davide; Marrano, Claudia; Ragni, Laura; Klein, Eva Maria; Vitale, Alessandro; Pedrazzini, Emanuela
Abstract: The rapid, massive synthesis of storage proteins that occurs during seed development stresses endoplasmic reticulum (ER) homeostasis, which activates the ER unfolded protein response (UPR). However, how different storage proteins contribute to UPR is not clear. We analyzed vegetative tissues of transgenic Arabidopsis ( Arabidopsis thaliana) plants constitutively expressing the common bean ( Phaseolus vulgaris ) soluble vacuolar storage protein PHASEOLIN (PHSL) or maize ( Zea mays) prolamins (27-kDa γ-zein or 16-kDa γ-zein) that participate in forming insoluble protein bodies in the ER. We show that 16-kDa γ-zein significantly activates the INOSITOL REQUIRING ENZYME1/BASIC LEUCINE ZIPPER 60 (bZIP60) UPR branch—but not the bZIP28 branch or autophagy—leading to induction of major UPR-controlled genes that encode folding helpers that function inside the ER. Protein blot analysis of IMMUNOGLOBULIN-BINDING PROTEIN (BIP) 1 and 2, BIP3, GLUCOSE REGULATED PROTEIN 94 (GRP94), and ER-localized DNAJ family 3A (ERDJ3A) polypeptides confirmed their higher accumulation in the plant expressing 16-kDa γ-zein. Expression of 27-kDa γ-zein significantly induced only BIP3 and ERDJ3A transcription even though an increase in GRP94 and BIP1/2 polypeptides also occurred in this plant. These results indicate a significant but weaker effect of 27-kDa γ-zein compared to 16-kDa γ-zein, which corresponds with the higher availability of 16-kDa γ-zein for BIP binding, and indicates subtle protein-specific modulations of plant UPR. None of the analyzed genes was significantly induced by PHSL or by a mutated, soluble form of 27-kDa γ-zein that traffics along the secretory pathway. Such variability in UPR induction may have influenced the evolution of storage proteins with different tissue and subcellular localization. Abstract : The evolution of seed storage proteins in grasses can be related to their increasing stress-inducing properties in the endoplasmic reticulum.